2010
DOI: 10.1099/mic.0.039180-0
|View full text |Cite
|
Sign up to set email alerts
|

Production of hydrogen sulfide by two enzymes associated with biosynthesis of homocysteine and lanthionine in Fusobacterium nucleatum subsp. nucleatum ATCC 25586

Abstract: Fusobacterium nucleatum produces a large amount of the toxic metabolite hydrogen sulfide in the oral cavity. Here, we report the molecular basis of F. nucleatum H2S production, which is associated with two different enzymes: the previously reported Cdl (Fn1220) and the newly identified Lcd (Fn0625). SDS-PAGE analysis with activity staining revealed that crude enzyme extracts from F. nucleatum ATCC 25586 contained three major H2S-producing proteins. Two of the proteins with low molecular masses migrated similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 45 publications
(48 reference statements)
2
55
1
Order By: Relevance
“…Further analysis of the amino acid sequences of cysteine synthase from the three species showed almost complete homologies with the sequence reported for cdl (Fn1220) in F. nucleatum . Yoshida and coworkers reported approximately 40% identity of the H 2 S producing gene Fn1220 from F. nucleatum to cysteine synthases A and B in E. coli and suggested that both these enzymes may catalyze both of the reactions that result in the production of H 2 S and L-lantionine and of L-cysteine and acetate respectively [15]. One can therefore assume that H 2 S production in different species of Fusobacterium is the result of the condensation of cysteine molecules with lanthionine as a byproduct.…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis of the amino acid sequences of cysteine synthase from the three species showed almost complete homologies with the sequence reported for cdl (Fn1220) in F. nucleatum . Yoshida and coworkers reported approximately 40% identity of the H 2 S producing gene Fn1220 from F. nucleatum to cysteine synthases A and B in E. coli and suggested that both these enzymes may catalyze both of the reactions that result in the production of H 2 S and L-lantionine and of L-cysteine and acetate respectively [15]. One can therefore assume that H 2 S production in different species of Fusobacterium is the result of the condensation of cysteine molecules with lanthionine as a byproduct.…”
Section: Discussionmentioning
confidence: 99%
“…Cell extracts showed enzymatic activity resulting in production of H 2 S from L-cysteine, while the cell membrane fraction displayed no such activity, indicating that the H 2 S-producing enzyme is located in the cytoplasm. Among oral bacteria, Fusobacterium species (32)(33)(34)(35) have been reported to possess cystathionine ␥-lyase (EC 4.4.1.1) (which cleaves L-cysteine to pyruvate, ammonia, and H 2 S at a ratio of 1:1:1), cystathionine ␤-synthase lyase (EC 4.2.1.22) (which cleaves L-cysteine to serine and H 2 S at a ratio of 1:1), and cysteine lyase (EC 4.4.1.10) (which catalyzes the synthesis of lanthionine and H 2 S at a ratio of 1:1 from 2 cysteines) (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, L- or D-cysteine desulfhydrase have been described in diverse taxa (Kumagai et al, 1975) including a few intestinal pathogens such as Salmonella thyphimurium (Kredich et al, 1972), Mycobacterium tuberculosis (Wheeler et al, 2005), H. pylori (Kim et al, 2006), and the protozoan Leishmania major (Nowicki et al, 2010). L- or D-cysteine desulfhydrase have also been studied in various oral microorganisms as a source of malodor and abscess formation (Igarashi et al, 2009; Yoshida et al, 2010, 2011). Those genera found in the oral cavity, namely Streptococcus, Prevotella and Fusobacterium , are also common inhabitants of the human colon.…”
Section: Microbial Pathways Involved In Colonic Sulfur Metabolismmentioning
confidence: 99%